Policy Implementation: Teachers’ Role as First Responders in Emergencies and Disasters - Hyder, Shabir; Manzoor, Adnan Fazal; Iqbal, Muhammad Amjad (UI Scholars Hub, 2020)
During the past decade, the schoolchildren faced many disasters and emergencies originating from natural and man-made sources. The safety of schoolchildren rests with school management and teachers. This study aimed to assess teachers' awareness with regard to disaster prevention and health, safety, security, and environment (HSSE) policies at primary schools in Pakistan. In addition, it explores the suitability of teachers to perform as emergency handlers in the absence of school nurses and resource officers (SROs). The study involved a qualitative study, based on open-ended interviews from a sample of 25 school teachers. Methodology triangulation was applied to reduce bias. Results revealed that the majority of teachers do not know about national policies related to school safety and security. Most of the teachers had been assigned additional roles as safety officers at the school, though they lack relevant training. Moreover, neither safety nor security aspects are incorporated into national educational policy. This study was the first study on Pakistani teachers’roles as emergency first responders. With the highest rate of attacks on educational institutions globally, the region still lacks a coherent policy structure. The study found numerous inconsistencies in public policies. It seeks to contribute to the literature to better understand the educational safety environment at both the ground and policy levels.